The influences of job satisfaction and organizational commitment on turnover intention - Primasheila, Debitri; Perizade, Badia; Hanafi, Agustina; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2022)
This study aimed to find out partially and simultaneously the influences of job satisfaction and organizational commitment on turnover intention of nursing staff at Bunda General Hospital Palembang. This study used qualitative data through questionnaire statements quantified using a Likert scale of 1-5 points to measure the attitudes, opinions, and perceptions. The total population was 144 people of which 20 of them were used in the survey before starting this study. Therefore, the number of samples was 124 people using the population sampling technique. The data were collected by using a questionnaire that had been tested for its validity and reliability with the result that it was reliable and usable. Multiple Regression Analysis Technique was used to analyze the collected data. The results of the study showed that partially the job satisfaction and organizational commitment had a significant influence on turnover intention; and simultaneously, had a negative and significant effect on turnover intention. The findings are expected to be used to improve the performance of nursing staff by providing authority according to task performance, recognition as appreciation for success in completing work well, and increasing organizational commitment to reduce the intention to quit or leave the company.